Биологическое разнообразие оксибионтов (в виде жизнеспособных спор) и анаэробов в донных осадках сероводородной батиали Черного моря - Зайцев, Ю.П.; Поликарпов, Г.Г.; Егоров, В.Н.; Гулин, С.Б.; Копытина, Н.И.; Курилов, А.В.; Нестерова, Д.А.; Нидзвецкая, Л.М.; Поликарпов, И.Г.; Стокозов, Н.А.; Теплинская, Н.Г.; Теренко, Л.М. (Видавничий дім "Академперіодика" НАН України, 2008)
From the bottom sediments of the Dnieper river palaeodelta in the north-western Black Sea at a depth of 730 m, cultures of heterotrophic bacteria (including oil oxidizing forms) and colliform bactera, unicellular algae (Bacillariophyta, Pyrophyta, Chlorophyta, Cyanophyta, Chrysophyta, Silicoflafellata), and higher fungi (Ascomycota and Anamorphic fungi) are obtained. No living invertebrates are found.